Acute Coronary Syndrome Treated with Percutaneous Coronary Intervention in Hutchinson-Gilford Progeria - Luciano De Simone; Serena Chiellino; Gaia Spaziani; Giulio Porcedda; Giovan Battista Calabri; Sergio Berti; Silvia Favilli; Laura Stefani; Giuseppe Santoro (MDPI AG, 2023)
Hutchinson-Gilford progeria syndrome is an extremely rare genetic disease caused by a de novo mutation in the LMNA gene, leading to an accumulation of a form of Lamin A, called Progerin, which results in a typical phenotype and a marked decrease in life expectancy, due to early atherosclerosis and cardiovascular disease. We report the case of a fourteen-year-old Chinese boy with Hutchinson-Gilford progeria syndrome admitted to the emergency room because of precordial pain. Physical examination showed tachycardia 130 beats/min and arterial hypertension: 170/120 mmHg, normal respiratory rate, no neurological impairment; ECG evidenced sinus tachycardia, left ventricular hypertrophy, horizontal ST-segment depression in I, aVL, II, III, aVF leads, and V4-V6 and ST-segment elevation in aVR and V1 leads. Echocardiography highlighted preserved global left ventricular function with concentric hypertrophy, altered diastolic flow pattern, mitral valve insufficiency, and minimal aortic regurgitation. Blood tests evidenced an increase in high-sensitivity troponin T level (335 pg/mL). NSTEMI diagnosis was performed, and the patient was admitted to the intensive care unit. A coronary CT angiography showed a severe obstruction of the common trunk of the left coronary artery, for which an urgent percutaneous coronary intervention (PCI) was proposed. A selective coronary angiography imaged complete chronic occlusion of the left main coronary artery as well as severe stenosis at the origin of a very enlarged right coronary artery that vascularized the left coronary artery through collaterals. Afterwards, the right coronary artery was probed using an Amplatz right (AR1) guiding catheter, through which a large 3.5 mm drug-eluting coronary stent (Xience Sierra, Abbott, Abbott Park, IL, USA) was implanted. At the end of the procedure, no residual stenosis was imaged and improved vascularization of the left coronary artery distribution segments was observed. Dual antiplatelet therapy (DAPT) consisting of aspirin (75 mg daily) and clopidogrel (37.5 mg daily) and anti-hypertensive therapy were started. At the one-year follow-up, the patient had not reported any occurrence of anginal chest pain.